Colorectal Cancer Screening With High Risk-Factor Questionnaire and Fecal Immunochemical Tests Among 5, 947, 986 Asymptomatic Population: A Population-Based Study - Zhang, Mingqing; Zhao, Lizhong; Zhang, Yongdan; Jing, Haoren; Wei, Lianbo; Li, Zhixuan; Zhang, Haixiang; Zhang, Yong; Zhu, Siwei; Zhang, Shiwu; Zhang, Xipeng (Frontiers in Oncology, 2022)
Background: The recent uptrend in colorectal cancer (CRC) incidence in China is causing an increasingly overwhelming social burden. And its occurrence can be effectively reduced by sensitizing CRC screening for early diagnosis and treatment. However, a large number of people in China do not undergo screening due to multiple factors. To address this issue, since 2012, a CRC screening program has been initiated in Tianjin. Methods: Residents aged 40-74 years were eligible for CRC screening. The first was to complete the high-risk factor questionnaire (HRFQ) and undergo fecal immunochemical test (FIT). Then those with a positive result in any of the two screening methods were recommended for a free colonoscopy. Results: The detection rate of intestinal diseases increased with age, had a male predominance, and was higher in residents from central urban areas and those with primary school above education level. The sensitivity of predicting CRC after colonoscopy in the high-risk group was 76.02%; the specificity was 25.33%.A significant decrease in the detection rate of intestinal disease, CRC and advanced adenoma was observed from positive FIT, the high-risk group and positive HRFQ , 47.13%, 44.79%, 42.30%; 3.15%, 2.44%, 1.76%; 7.72%, 6.42%, 5.08%, in that order, while no inter-group difference was found for the detection of polyps. In addition, the different combinations of HRFQ and FIT can enroll more high-risk population than FIT or (and) HRFQ only , and thus detect more intestinal diseases (include CRC/AA/Polyp). Conclusion: The superimposition of different screening method for HRFQ and FIT is an effective strategy for the detection of CRC, AA, and Polyp, compared to HRFQ or FIT alone. However, further improvements in screening and interventions are needed to promote colonoscopy compliance.